Factors Relating to the Expectations and Perceptions of Post-Stroke Outpatients’ in the Rehabilitation Services of Bangladesh - Hasan, Mohammad Shaikhul; Anusaksathien, Kantabhat; Narattharaksa, Kanida; Afrin, Nahar (International Journal of Statistics in Medical Research, 2022)
Purpose: For enhancing patients’ participation, this study aims to identify the patient-related factors that relate to the expectations and perceptions of post-stroke outpatients’ in the rehabilitation services of Bangladesh. Methods: A questionnaire survey was administered to 342 outpatients from the stroke rehabilitation department. Descriptive statistical analysis was applied to measure patients’ perceptions and expectations. Eta statistic from ANOVA was applied to examine the relationship between patient-related factors and the patients’ expectations and perceptions of the rehabilitation services. Findings: Patients’ expectations rated higher than the perceptions in all the dimensions of rehabilitation services. Factors such as; (i) patients' education (0.222, p=0.005) and post-stroke disability (0.447, p<0.001) indicated a significant relationship with patients' expectations. (ii) Patients' education (0.210, p=0.010), occupation (0.226, p=0.003), family status (0.180, p=0.048) and daily activities before the stroke (0.169, p=0.044), post-stroke disability (0.195, p=0.004) and distance from home to the hospital (0.190, p=0.006) indicated a significant relationship with their perceptions in the rehabilitation services. Conclusion: The findings of this study concluded that the rehabilitation manager needs to work on these factors and recommended developing a continuing education program to minimize these factors of poor perceptions in the rehabilitation services.